Frederich Schlegel and the Fragmentary Self of Romantic Psychology - Reid, Jeffrey (Université d'Ottawa | University of Ottawa, 2019)
Romantic psychology is first specified in counter-distinction to Enlightenment-informed faculty-psychology, whose scientific paradigm is fundamentally materialistic and mechanistic. Romantic psychology is then presented through Fr. Schlegel’s theory and practice of the literary fragment. In the fragment, we discover selfhood that is self-positing, powered by electro-chemical forces and enlivened by the stimulating Other. Romantic psychology determines the self as an ironic system, complete and yet organically open to other selves. It is phenomenological in nature and its contemporary legacy can be found in psychoanalysis and psychoanalytical hermeneutics.
Keywords: faculty psychology; early german romanticism; irony; romantic fragment